Pemberian Rebusan Daun Binahong Terhadap Kadar Asam Urat Pasien Gout Arthritis - Winda Winda; Gusman Virgo; Nia Aprilla (Excellent Health Journal, 2025)
ABSTRACT Problems that can occur if someone has gouty arthritis include permanent joint damage, the appearance of lumps (tophi) under the skin, kidney stones, and even kidney failure if this condition is not treated properly. In addition, this disease can also increase the risk of other chronic diseases such as high blood pressure/hypertension. High uric acid levels are indirectly associated with an increased risk of cardiovascular diseases, such as coronary heart disease and stroke, as they can damage blood vessel linings. Chronic pain, limited mobility, and other health problems can significantly reduce quality of life. The purpose of this study was to determine the difference in uric acid levels before and after administering a decoction of binahong leaves. This study was conducted in Kualu Nenas Village, Tambang Community Health Center Working Area. This study was a qualitative descriptive study. This study was conducted from June 22-24, 2025. The main complaints experienced by the client were joint pain, especially at night, swelling of the right foot, difficulty walking, and redness. The pain felt like being pricked by needles. The client also complained of difficulty falling asleep, stating that sleep was restless and she often woke up at night. During the day, the client also had difficulty sleeping. The uric acid level test result was 7.2 mg/dl. Vital signs were as follows: BP: 135/95 mmHg, HR: 92 beats per minute, RR: 20 breaths per minute, temperature: 36.7°C. The intervention provided by the researcher was the administration of boiled binahong leaf water to reduce uric acid levels in patients with gouty arthritis. The results showed a decrease in uric acid levels after administering boiled binahong leaf water twice a day. It is hoped that clients and their families will continue to consume boiled binahong leaf water if uric acid levels increase.